Biomarker responses in fish exposed to polycyclic aromatic hydrocarbons (PAHs): Systematic review and meta-analysis. (November 2018) - Santana, Manuela S.; Sandrini-Neto, Leonardo; Filipak Neto, Francisco; Oliveira Ribeiro, Ciro A.; Di Domenico, Maikon; Prodocimo, Maritana M.
Abstract: Biomarkers of antioxidant and biotransformation systems are commonly used to assess polycyclic aromatic hydrocarbons (PAHs) pollution in fish. Despite their extensive application of biomarkers, contradictory results are vastly reported in the literature, even for the same species in similar contamination scenarios. This study aims to verify response patterns of biomarkers in fish exposed to PAHs. Through systematic reviews and meta-analyses, we were able to evaluate: (i) overall magnitude of PAHs effects on biotransformation and oxidative stress biomarkers; (ii) patterns of response among experimental approaches (laboratory, field and active biomonitoring), environment (marine and freshwater) and fish habitat (pelagic, demersal, etc.); (iii) effects of exposure route, time and concentration of PAHs; and ( iv ) which biomarkers respond best to PAHs exposure. Overall, biomarker responses were significantly affected by PAHs exposure. The activities of ethoxyresorufin-O-deethylase (EROD), glutathione S-transferase (GST), superoxide dismutase (SOD), glutathione peroxidase (GPx) and levels of oxidized glutathione (GSSG) and lipid peroxide (LPO) significantly increased in fish exposed to PAHs, whereas catalase (CAT) and glutathione reductase (GR) activities and levels of reduced glutathione (GSH) were not affected. Amongst responsive biomarkers, EROD and GST activities significantly differed among approaches and between marine and freshwater environments, but were not affected by fish habitat. GSSG levels were higher in fish from laboratory bioassays compared to the field, but did not differ between environments nor habitats. Exposure route played a major role only for GST and GPx responses. Finally, increasing PAHs concentration and exposure time had a significant effect on all assessed biomarkers, except for CAT. We conclude that EROD and GST are robust biomarkers to assess PAHs effects in fish. Contrarily, CAT is an inadequate biomarker of PAHs exposure since no significant response was observed. Our study also highlighted some research gaps in PAHs contamination studies, such as a clear lack of active biomonitoring experiments. Graphical abstract: Image 1 Highlights: Fish biotransformation and oxidative stress biomarkers were meta-analytically assessed. Overall biomarker responses were significantly affected by PAHs exposure. Effects were stronger in laboratory than field and active biomonitoring studies. Type of environment, fish habitat and exposure route did not affect most responses. Generally, biomarkers responded to increasing exposure time and concentration of PAHs. Abstract : Meta-analyses of PAHs effects on fish biomarkers.